Transcriptional Factor NF-κB as a Target for Therapy in Parkinson's Disease - Patrick M. Flood; Li Qian; Lynda J. Peterson; Feng Zhang; Jing-Shan Shi; Hui-Ming Gao; Jau-Shyong Hong (Parkinson's Disease)
Parkinson's disease (PD) is a neurodegenerative condition characterized by chronic inflammation. Nuclear factor κB (NF-κB) is a family of inducible transcription factors that are expressed in a wide variety of cells and tissues, including microglia, astrocytes, and neurons, and the classical NF-κB pathway plays a key role in the activation and regulation of inflammatory mediator production during inflammation. Activation of the classical NF-κB pathway is mediated through the activity of the IKK kinase complex, which consists of a heterotrimer of IKKα, IKKβ, and IKKγ subunits. Targeting NF-κB has been proposed as an approach to the treatment of acute and chronic inflammatory conditions, and the use of inhibitors specific for either IKKβ or IKKγ has now been found to inhibit neurodegeneration of TH+ DA-producing neurons in murine and primate models of Parkinson's disease. These studies suggest that targeting the classical pathway of NF-κB through the inhibition of the IKK complex can serve as a useful therapeutic approach to the treatment of PD.